Hydrogen from industrial aluminium scraps: Hydrolysis under various conditions, modelling of pH behaviour and analysis of reaction by-product - Urbonavicius, Marius; Varnagiris, Sarunas; Mezulis, Ansis; Lesnicenoks, Peteris; Knoks, Ainars; Richter, Christiaan; Milcius, Darius; Meirbekova, Rauan; Gunnarsson, Gudmundur; Kleperis, Janis (Elsevier, 2023)
The study explores the feasibility of utilizing aluminium scrap waste from the construction industry for hydrogen production via hydrolysis. Specifically, the study involves a primary analysis of aluminium scrap waste and the impact of various reaction parameters, such as NaOH molarity, reaction temperature, amount of Al scrap, solvent quantity, and the reaction vessel insulation, and their effects on the reaction rate, H2 yield, and by-product formation. The pH of the reaction solution was continuously monitored to determine the reaction mechanism, while the structure of the by-product was analysed at two stages: after removal and drying, and after removal and washing. Our findings indicate that increasing the reaction temperature has the most significant influence on the reaction kinetics. Insulating the reaction vessel ensured self-promoted hydrogen production due to the heat generated from the exothermic reaction inside the vessel, resulting in an approximate temperature increase of 5 °C for all tested reaction solution molarities compared to non-insulated conditions. The pH measurements were conducted in two different ways. The first one involved immersing a pH probe directly into an open reaction container. The second approach utilized a closed reaction container under isothermal conditions, where both the pH and H2 yield were measured simultaneously. In addition, the obtained data was compared between the measured pH values and the predictions generated by models utilizing the measured H2 evolution in order to forecast the pH behaviour. The modelling results recognize and suggest the existence of separate reaction phases or zones, each characterized by distinct influences on the pH level. --//-- Marius Urbonavicius, Sarunas Varnagiris, Ansis Mezulis, Peteris Lesnicenoks, Ainars Knoks, Christiaan Richter, Darius Milcius, Rauan Meirbekova, Gudmundur Gunnarsson, Janis Kleperis, Hydrogen from industrial aluminium scraps: Hydrolysis under various conditions, modelling of pH behaviour and analysis of reaction by-product, International Journal of Hydrogen Energy, 2023, ISSN 0360-3199, https://doi.org/10.1016/j.ijhydene.2023.09.065. (https://www.sciencedirect.com/science/article/pii/S0360319923046323) Published under the CC BY-NC-ND licence.
This research is funded by the Baltic Research Programme project No. EEA-RESEARCH-92 “Aluminum in circle economy - from waste through hydrogen energy to alumina” – AliCE-Why” under the EEA Grant of Iceland, Liechtenstein and Norway (No. EEZ/BPP/VIAA/2021/5); EU CAMART2 project (European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508).
Keywords: Hydrogen generation; Hydrolysis; Waste aluminium; Arrhenius calculation; Alkali solution; pH modelling